Thermal EHL analysis of the inner ring rib and roller end in tapered roller bearings with the Carreau model - Liu, Xiaoling; Long, Tao; Li, Xinming; Guo, Feng (Frontiers in Manufacturing Technology, 2023)
The roller end/rib contact of tapered roller bearings significantly affects lubricating condition and power loss. To improve the lubrication performance of the inner ring rib and the large end of the roller in tapered roller bearings used in railway coaches, based on the structural analysis of the inner rib and the large end of the roller, considering spin-slide effects between the rib and the large end of the roller, thermal elastohydrodynamic lubrication (EHL) model with Carreau rheological model was established in a tapered roller bearing. Two kinds of rib structures were provided, i.e., tapered rib and spherical rib. Under different conditions, variations in the friction coefficient versus the ratio of curvature radius of large end of the roller to that of the rib were compared, and the film thickness and film temperature varied with the rotational speed and the load was in comparison for the two rib structures. Results show that, spinning motion has little effect on the lubrication at the contact point between the inner ring rib and the large end of tapered roller. There is an optimal ratio of the curvature radius between the large end of the roller and the spherical or the tapered rib, moreover, the friction coefficient corresponding to this optimal ratio value is the smallest. With the increase of the inner ring speed, both the film thickness and temperature increase for the two rib structures. Different from the spherical rib, the difference between the minimum and the central film thickness is almost unchanged, and the temperature rise slightly increases for the tapered rib. As the load increases, the difference between the minimum and the central film thickness becomes larger, and the temperature in the contact zone gradually increases for the two ribs. Different from the tapered rib, lower frictional coefficient and less minimum film thickness are generated for the spherical rib because of higher film temperature.